Magnetoelectric Coupling Triggered by Noncollinear Magnetic Structure in M‐Type Hexaferrite. Issue 4 (22nd February 2021) - Shao, Ye; Huang, Fengzhen; Zhang, Junting; Yan, Shuo; Xiao, Shuyu; Lu, Xiaomei; Zhu, Jinsong
Abstract: Direct magnetoelectric (ME) coupling between magnetic and ferroelectric orders, which can be realized in spiral magnets, is vital in technological applications of multifunctional materials. Multisusceptible BaFe12 O19 is noteworthy for its excellent magnetic, dielectric properties and thus the application in high‐density information storage, while its collinear spin structure limits the emergence of ferroelectrics and ME coupling. In this work, nonzero Dzyaloshinskii–Moriya (DM) interaction is created by partial substitution of the spin‐down Fe 3+ sites to induce conical spin structure in BaFe12 O19 . Larger In 3+ ions are introduced and prefer to occupy the spin‐down 4 f 1 and 4 f 2 lattice sites. The evolution of magnetization versus temperature adduces evidence of conical magnetic structure. As a result, direct ME and magnetodielectric coupling are obtained in In‐doped BaFe12 O19 ceramics. An interlayer DM interaction model is built to discuss the intrinsic relationship among crystal structure, noncollinear magnetic structure, and ionic substitution. Moreover, BaZn0.9 Zr0.9 Fe10.2 O19 ceramics are also prepared, and exhibit noncollinear magnetic structure and direct ME coupling since Zn 2+ and Zr 4+ also possess larger radii than Fe 3+ and prefer to enter the spin‐down sites. The present result provides a feasible avenue to develop multiferroic and magnetoelectric coupling in ubiquitous M‐type hexaferrite. Abstract : Conical magnetic structure together with direct and repeatable magnetoelectric coupling are induced by partial substitution of the spin‐down Fe 3+ sites in M‐type barium hexaferrite. An interlayer Dzyaloshinskii–Moriya (DM) interaction model is proposed and it reveals that nonzero DM interaction can be formed due to the local uncompensated DM vector and be responsible for the conical magnetic structure.